Environmental (in)justice in the Anthropocene ocean. (January 2023) - Bennett, Nathan J.; Alava, Juan José; Ferguson, Caroline E.; Blythe, Jessica; Morgera, Elisa; Boyd, David; Côté, Isabelle M.
Abstract: Environmental justice refers broadly to the distribution of environmental benefits and burdens, and the fair treatment and meaningful involvement of all people in environmental decision-making and legal frameworks. The field of environmental justice initially developed out of a concern for the disproportionate distribution and impacts of environmental pollution and hazardous waste disposal on groups that have been historically and structurally marginalized, including Black populations and socio-economically disadvantaged communities. More recent environmental justice scholarship has expanded geographically and focused on a broader set of environmental hazards and harms, such as climate change impacts, biodiversity and habitat loss, and ecosystem service declines. Yet, the impacts and distribution of environmental hazards and harms in the marine environment on coastal populations has received less attention in the environmental justice literature. This narrative review paper starts to address this gap through a focus on five main areas of environmental injustice in the ocean: 1) pollution and toxic wastes, 2) plastics and marine debris, 3) climate change, 4) ecosystem, biodiversity and ecosystem service degradation, and 5) fisheries declines. For each, we characterize the issue and root drivers, then examine social and distributional impacts. In the discussion, we explore how these environmental injustices are converging and interacting, cumulative, differentiated, and geographically distributed, and briefly examine solutions and future research directions. In conclusion, we call for greater and more explicit attention to environmental justice in ocean research and policy. Graphical Abstract: ga1 Highlights: There is a substantial and growing body of literature on environmental justice. Yet, environmental justice issues in the oceans have received less attention. Issues include pollution, plastics, climate change, ecosystem services and fisheries. We examine the social and distributional impacts of these marine hazards and harms. Environmental injustices in the ocean are growing, differentiated and converging.